1984
DOI: 10.3758/bf03333865
|View full text |Cite
|
Sign up to set email alerts
|

Color preference as a function of the object described

Abstract: Noting the inconsistent research on the relationship between color and personality, the authors present data on one of the possible reasons for the problem. The problem addressed is that color/personality research almost always presents a color patch or patches and draws inferences from the subjects' choices, ignoring the possibility that color preference is related to the object in question. College students were asked to give their favorite colors for a number of items (e.g., automobile). The results clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 8 publications
5
53
0
1
Order By: Relevance
“…Color associations are context dependent and depend on the product (Grossman & Wisenblit, 1999;Holmes & Buchanan, 1984). On this note, Grossman and Wisenblit (1999) suggested that the twofold component of color may be seen in the view of associative learning; consumers create attitudes through a belief formation of a cognitive process and through an emotional process in terms of a affect transfer (Kim, Allen, & Kardes, 1996).…”
Section: Congruence Versus Incongruence For Product Design and Colormentioning
confidence: 99%
“…Color associations are context dependent and depend on the product (Grossman & Wisenblit, 1999;Holmes & Buchanan, 1984). On this note, Grossman and Wisenblit (1999) suggested that the twofold component of color may be seen in the view of associative learning; consumers create attitudes through a belief formation of a cognitive process and through an emotional process in terms of a affect transfer (Kim, Allen, & Kardes, 1996).…”
Section: Congruence Versus Incongruence For Product Design and Colormentioning
confidence: 99%
“…Color preferences can and do vary for different kinds of objects (Holmes & Buchanan, 1984;Saito, 1983;Schloss et al, 2013;Taft, 1997), and we refer the interested reader to Schloss et al (2013) for a discussion of the relative contributions of the ecological, functional, and personal factors that account for preferences for the colors of particular objects.…”
Section: An Ecological Account Of Individual Differencesmentioning
confidence: 99%
“…In addition to this, effects of the single attributes of the label including the possible influence of colour-coded nutrition information on food choice have not been examined in detail. Concerning the use of colours in consumer choice, decision making and purchase behaviour, studies from related areas of research have focused on the effects of colour coding and the images conveyed by different colours (36)(37)(38)(39)(40) . It is noted (p. 41) that 'colours are known to possess emotional and psychological properties.…”
mentioning
confidence: 99%